2008
DOI: 10.1097/inf.0b013e31816b4539
|View full text |Cite
|
Sign up to set email alerts
|

Double Boosted Protease Inhibitors, Saquinavir, and Lopinavir/Ritonavir, in Nucleoside Pretreated Children at 48 Weeks

Abstract: Double boosted SQV/LPV/r resulted in significant CD4 rise and VL decline at 48 weeks. Hyperlipidemia was common. Cmin of both PIs exceeded therapeutic concentrations. Poor adherence caused failure in 10%. No major PI mutations were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
(18 reference statements)
3
16
0
Order By: Relevance
“…The pediatric HIV-NAT 017 study which treated children with second-line SQV and LPV/r reported a viral suppression rate similar to that observed in our study with 64% having HIV RNA < 50 copies/ml at week 48 [21]. A non-randomized study in Thai adults showed that the double-boosted PI regimen was not as potent in suppressing HIV RNA to below 50 copies/ml when compared to the single-boosted PI regimen among patients with low grade multi- NRTI resistance mutations [22].…”
Section: Discussionsupporting
confidence: 82%
“…The pediatric HIV-NAT 017 study which treated children with second-line SQV and LPV/r reported a viral suppression rate similar to that observed in our study with 64% having HIV RNA < 50 copies/ml at week 48 [21]. A non-randomized study in Thai adults showed that the double-boosted PI regimen was not as potent in suppressing HIV RNA to below 50 copies/ml when compared to the single-boosted PI regimen among patients with low grade multi- NRTI resistance mutations [22].…”
Section: Discussionsupporting
confidence: 82%
“…Our results showed a similar efficacy compared to the other two available studies of double-boosted PI in experienced HIV-infected children. These two studies assessed the efficacy of the combination of SQV and LPV/r in a cohort of 50 HIV-infected children; the first and the second assessment were performed at week 48 and 96 respectively [13,14]. At week 48 the median CD4 increase was 9% (IQR 5-16) and the percentage of patients with HIV-RNA < 400 and < 50 copies/ml were 78 and 64, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent studies showed that dual-boosted SQV and LPV may be an effective and safe alternative for a second-line regimen in pre-treated children, nevertheless a close follow up is necessary because dislipidemia can occur during treatment [13,14]. Therefore, we decided to test this therapeutic option in a long term observational cohort of 7 HIV-infected children.…”
Section: Introductionmentioning
confidence: 99%
“…In children who failed an NRTI/NNRTI based HAART regimen, a double boosted PI regimen (SQV and LPV/r) was demonstrated to have strong virological and immunological response after 48 weeks and 96 weeks [31,50]. However, as mentioned before, the C min of both PIs were higher than the therapeutic concentrations, resulting in elevated lipids and suggesting further exploration of the possibility of dose reduction of PI in children.…”
Section: Introductionmentioning
confidence: 99%